Outcomes of a Coaching-Based WHO Safe Childbirth Checklist Program in India. Issue 5 (May 2018) - Semrau, Katherine E. A.; Hirschhorn, Lisa R.; Delaney, Megan Marx; Singh, Vinay P.; Saurastri, Rajiv; Sharma, Narender; Tuller, Danielle E.; Firestone, Rebecca; Lipsitz, Stuart; Dhingra-Kumar, Neelam; Kodkany, Bhalachandra S.; Kumar, Vishwajeet; et al.
Abstract : (Abstracted from N Engl J Med 2017;377:2313–2324) In recent decades, there has been a dramatic shift from home to facility-based births, as well as an overall reduction in birth-related mortality. Despite these trends, a large disparity exists in maternal and neonatal mortality between countries that is directly related to their economies.